Value Added per Worker, Capital Accumulation, and Technical Progress (The Pakistan Development Review, 1988)
Within the context of industrial restructuring, it is not uncommon to use terms such as 'higher value-added per worker', or 'low or high value added activities', and 'high technology' industries. The present note attempt to use the theoretical work in the field of international trade to sharpen our understanding of the relationships among the concepts of value added per worker. capital accumulation, and technical progress. We show that for a large country, capital accumulation raises the real value added per worker in both industries. With neutral technical progress occurring in the L-intensive industry, it is possible for the terms of trade effect to lead to a decline in Real labour productivity,